Home Visit as A Strategy to Increase Access to Primary Health Care: A Scoping Review - Aditia Putri; Dumilah Ayuningtyas (Jurnal Kesehatan Manarang, 2023)
Primary Health Care (PHC) is a foundation of universal health coverage for enabling equitable access. However, the access barrier is one of the challenges in implementing PHC. Home visits becomes one of the PHC innovations in several countries. This review aimed to describe home visit implementation in various countries regarding the scope, and service providers to achieve the expected impacts. This descriptive study used scoping review method referring to Arksey and O’Malley’s guidelines. Three databases, which are PubMed, ProQuest, and Embase, were searched using keywords, namely “home visit” and “primary health care” or “primary healthcare” or “PHC services”. The articles’ identification used the PRISMA method. From the search result that was limited to 2002-2022, 367 articles were retrieved and screened for titles and abstracts, resulting in 48 full-text articles for eligibility assessment. Finally, ten studies were further analyzed and synthesized according to the study’s aim. The scope of home visits is a comprehensive life cycle approach. Services providers are community health workers, nurses, midwives, doctors, and multidisciplinary teams. The impact of home visits is increasing knowledge and healthy behaviour, utilization, service quality, and health status as well as encouraging cross-sectoral collaboration and interprofessional collaboration. The scope and the impact of the home visit were then categorized based on the three PHC components according to WHO. This research result can be used as input in the development of evidence-based policies for the implementation of home visits as part of the services provided by first-level health facilities with adjustments to the context in Indonesia.